Achieving inclusive microfinance: recommendations from Catholic Social Teaching and economic development literature - Gallenstein, Richard A. (Journal of management, spirituality & religion, 2023)
Microfinance programs are promoted as powerful tools for increasing financial inclusion and reducing poverty in the developing world. While these programs have shown promise, they often fail to reach the most marginalized potential clients and can actually increase exclusion through mechanisms such as social sanctions. In this paper, we review recent microfinance literature highlighting the benefits, drawbacks, and potential mechanisms of exclusion inherent in current microfinance models. We then outline principles, rooted in Catholic Social Teaching, that provide a fuller understanding of the human person and can help inform a more inclusive version of microfinance. Finally, we apply these principles and recent innovations in the economics literature to propose a list of practical recommendations for inclusive microfinance to achieve integral development.